Act of Nov. 18, 1858, in 1 The Laws of the Corporation of the City of Washington 418 (1868) - (:unkn) unknown (My University, 1858)
It shall not be lawful for any person or persons to carry or have concealed about their persons any deadly or dangerous weapons, such as dagger, pistol, bowie knife, dirk knife, or dirk, colt, slungshot, or brass or other metal knuckles within the City of Washington
Keywords: CARRY